FREQUENCY OF PULMONARY HYPERTENSION USING ECHOCARDIOGRAPHY IN PATIENTS OF IDIOPATHIC PULMONARY FIBROSIS AT A TERTIARY CARE HOSPITAL - Hassaan, Muhammad; Ajmal, Maliha; Butt, Nauman Ismat; Aftab, Sabeen; Ashfaq, Fahmina; Tareen, Muhammad Qasim (Journal of Postgraduate Medical Institute, 2022)
Objective: To determine the frequency of pulmonary hypertension among patients with idiopathic pulmonary fibrosis using echocardiography, presenting to the Pulmonology Department of a tertiary care hospital. Methodology: This cross-sectional study was conducted on a sample size of 130 patients (aged 50-80 years) with idiopathic pulmonary fibrosis presented to the Department of Pulmonology, Jinnah Hospital Lahore from September 2018 to March 2019. Mean pulmonary artery pressure (mPAP) 25 mmHg at rest was regarded to be pulmonary hypertension, whilst mPAP of 25–40 mmHg at rest was deemed to be moderate pulmonary hypertension, and mPAP >40 mmHg at rest was considered to be a serious disease. Data was analyzed using SPSS v.17.0. Numerical variables were summarized as mean and standard deviation. Chi-square test was used as a test of significance and a p-value < 0.05 was considered as significant. Results: Mean age was 64.5+8.7 years with 67 (51.5%) male and 63 (48.5%) female. The mean duration of the disease since diagnosis of Idiopathic Pulmonary Fibrosis was 13.6+6.4 months. After doing echocardiography, pulmonary hypertension was found in 19 (14.6%) patients with moderate pulmonary hypertension in 14 (10.7%) while 5 (3.8%) had severe disease. Mean mPAP was 19.2+9.2 mmHg (mPAP 10-50 mmHg). Conclusion: Pulmonary Hypertension is not an uncommon finding in patients with Idiopathic Interstitial Fibrosis. Prevalence of pulmonary hypertension had no association with the finding of this study. Moreover, no association of age, sex, or duration of disease with the prevalence of pulmonary hypertension was seen.